A nucleação de escolas do campo e o enfraquecimento das relações sociais nas comunidades camponesas - MENEZES, Luciano de Souza (2021)
This article / essay has as main objective to analyze the process of nucleation of rural schools from the reality of a rural school in the condition of being attached to a polo school, in the municipality of Medicilândia, state of Pará, and, therefore, the possible changes in social relations within this community, as well as the process of grouping them, and how the consequences of such a decision to intervene in government action affect the community as a whole. In this sense, we bring to the debate the perceptions of educational social actors directly involved or impacted by the referred decision-making by state agents, notably the municipal education secretaries, family members of students, students and teachers from the involved peasant communities and / or impacted by such a decision. Thus, it is important to know whether, and to what extent, the legal determinations provided for in the constitution are taken into account, how they directly or indirectly affect community members, and, notably, how and / or if collectively, the space and conditions are constituted. suitable for the dialogue between the agents of the public power and the leaders of the community aiming at the joint decision making that precedes the decision on the closure of schools in the countryside, rule or legal principle foreseen in specific legislation on the referred theme.